Reply to Van Overmeire, R. Comment on “Tyson, G.; Wild, J. Post-Traumatic Stress Disorder Symptoms among Journalists Repeatedly Covering COVID-19 News. Int. J. Environ. Res. Public Health 2021, 18, 8536” - Gabriella Tyson (MDPI AG, 2021)
During the COVID-19 pandemic, journalists reporting on the crisis in the UK were classed as keyworkers [...]